Comparison of the effects of different physical stimulation therapies on reducing upper limb spastic paralysis and motor dysfunction in stroke survivors after stroke: a network meta-analysis of randomized controlled trials - Bian, Mingtong; Chen, Fuyan; Su, Huizhen; Li, Zhiying; Sun, Xiaowei; Liu, Yang; Shi, Jinyuan; Liu, Shuo; Rong, Ru (Frontiers in Neurology, 2025)
BackgroundUpper limb spasticity is a common and disabling sequela of stroke, which significantly impairing motor function and the capacity to perform activities of daily living (ADL). The relative efficacy of different physical therapies and their combinations compared to monotherapies remains unclear.MethodsA comprehensive database search was conducted to identify randomized controlled trials (RCTs) published from database inception to 2024 that evaluated physical therapies for post-stroke upper limb spasticity. Data were analyzed using RevMan and STATA/R software with a Bayesian framework for network meta-analysis. Evidence consistency was assessed via node-splitting approaches, and intervention efficacy was ranked using the surface under the cumulative ranking curve (SUCRA). Effect sizes were expressed as mean differences (MD) with 95% confidence intervals (CI), and study quality was evaluated using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) system.ResultsForty-nine RCTs involving 3,219 patients were included. The combination of physical rehabilitation (PR) with repetitive transcranial magnetic stimulation (rTMS) and electro-acupuncture (EA) demonstrated the highest improvement in Fugl-Meyer Assessment for Upper Extremity (FMA-UE) scores (91.1%), outperforming PR alone (13.2%) or EA monotherapy (30.3%). PR combined with rTMS and body acupuncture (BA) shows the most significant improvement in the Modified Barthel Index (MBI) (83.1%), superior to PR (20.8%) or BA (23.8%) alone. Adverse events (e.g., minor bruising from EA) were infrequent and self-resolving.ConclusionCurrent evidence indicates that synergistic application of PR with rTMS and acupuncture (EA/BA) significantly enhances upper limb motor function and ADL capacity. However, GRADE evaluations rated most evidence as moderate quality, limited by implementation bias, insufficient subgroup analyses, and lack of long-term follow-up data. Future studies should adopt standardized protocols and investigate efficacy variations across stroke subtypes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025633289, identifier [CRD42025633289].